2018
DOI: 10.4062/biomolther.2018.001
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell Differentiation Using Microfluidic Device-Generated Growth Factor Gradient

Abstract: Neural stem cells (NSCs) have the ability to self-renew and differentiate into multiple nervous system cell types. During embryonic development, the concentrations of soluble biological molecules have a critical role in controlling cell proliferation, migration, differentiation and apoptosis. In an effort to find optimal culture conditions for the generation of desired cell types in vitro, we used a microfluidic chip-generated growth factor gradient system. In the current study, NSCs in the microfluidic device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Thus, the protocols need to be optimized before they can be applied in regenerative medicine. Recently, in addition to soluble factors that are required for proper cell development, culture dish surfaces and microfluidic chambers that are effective in generating gradients of soluble factors have also been studied to identify the optimal environment for SC culture and differentiation (Cha et al ., 2017; Kim et al ., 2018).…”
Section: Nscs/npcs For Neurodegenerative Diseasesmentioning
confidence: 99%
“…Thus, the protocols need to be optimized before they can be applied in regenerative medicine. Recently, in addition to soluble factors that are required for proper cell development, culture dish surfaces and microfluidic chambers that are effective in generating gradients of soluble factors have also been studied to identify the optimal environment for SC culture and differentiation (Cha et al ., 2017; Kim et al ., 2018).…”
Section: Nscs/npcs For Neurodegenerative Diseasesmentioning
confidence: 99%
“…Results interestingly confirmed that the proliferation and differentiation of hNSCs were directly depended on GF concentration. [4,22] Many other bio-molecules can influence the differentiation of stem cells based on their physiologic role in specific organs in vivo.…”
Section: Role Of Microfluidic Devices In Neural Differentiationmentioning
confidence: 99%
“…Stem cells are widely considered as biopharmaceuticals and cell therapies due to their potential proliferation, genetic modification with external gene delivery systems, and differentiation to neurons, astrocytes, and oligodendrocytes. [4] Consequently, inducing the differentiation of stem cells toward neural cell lineages plays an important role in the repairing process. There are 3 main types of stem cells involved in trans-differentiation studies and cellular replacement therapy including embryonic stem cells (ESC), adult stem cells (ASC), and induced pluripotent stem cells (iPSC).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been confirmed that DPSCs can be induced to form neurospheres or differentiate into mature neurons by endogenous signaling cues ( Heng et al, 2016 ). Many factors, for instance, the extracellular matrix, mechanical force, growth factors, culture systems, oxygen stress, and microfluidic systems, have been reported as critical factors for the induction of neuronal differentiation ( Heng et al, 2016 ; Thompson and Chan, 2016 ; Yamazaki et al, 2016 ; Kim et al, 2018 ; Liu et al, 2020 ). However, few in-depth studies have examined the effects of the surrounding microenvironment on the survival, proliferation, and expression of markers of DPSC post-neuronal differentiation.…”
Section: Introductionmentioning
confidence: 99%